Application of TAM model to the use of information technology - ., Harryanto; Muchran, Muchriana; Saleh Ahmar, Ansari (International Journal of Engineering and Technology, 2018)
The purpose of this research is to see the application of modified TAM model by entering the experiential variable as a moderation variable to see one's intention in the use of technology especially internet banking. Data obtained through the distribution of questionnaires to cus-tomers. The study population is bank customers registered as users of internet banking services. The sample selection used a simple random sampling technique. Hypothesis testing using Partial Least Square (PLS) method through AMOS program. The results showed that the proposed five hypothesis, two significant and three insignificant. Perceived ease of use is significantly related to perceived usefulness. Per-ceived usefulness is not significantly related to intention to use. Perceived ease of use is significantly related to intention to use moderated by experience and not significantly correlated with intention to use moderated by the Experience.Â